Agile adoption challenges in insurance: a systematic literature and expert review - Krishna Yudhakusuma Putra Munandar; Teguh Raharjo (Computer Science and Information Technologies, 2023)
The drawback of agile is struggled to function in large businesses like banks, insurance companies, and government agencies, which are frequently associated with cumbersome processes. Traditional software development techniques were cumbersome and pay more attention to standardization and industry, this leads to high costs and prolonged costs. The insurance company does not embrace change and agility may find themselves distracted and lose customers to agile competitors who are more relevant and customer-centric. Thus, to investigate the challenges and to recognize the prospect of agile adoption in insurance industry, a systematic literature review (SLR) in this study was organized and validated by expert review from professional with expertise in agile. The project performance domain from project management body of knowledge (PMBOK) was applied to align the challenges and the solution. Academicians and practitioners can acquire the perception and knowledge in having exceeded understanding about the challenge and solution of agile adoption from the results.